Monitoring the puerperium microbiota is a necessary condition for diagnosing newborn infections in the early neonatal period - L.G. Boronina; E.V. Samatova; A.G. Asnovskaya; S.A. Panova; S.S. Ustyugova; K.V. Zakharchuk (LCC «Medicine-Inform», 2023)
L.G. Boronina1,2, E.V. Samatova2, A.G. Asnovskaya2, S.A. Panova2, S.S. Ustyugova2, K.V. Zakharchuk2 1Ural State Medical University, Yekaterinburg, Russian Federation 2Regional Children's Clinical Hospital, Yekaterinburg, Russian Federation Background: maternal and child healthcare is considered a priority area of the public health services in all countries. Aim: to assess the birth canal microbiota in pregnant women and puerperia for diagnosing potential infections of newborn infants in the early neonatal period. Patients and Methods: this retrospective study analyses the results of microbiological examination of the samples taken from various loci of 1915 pregnant women and/or puerperia and newborn infants in the period of February 1, 2020, to February 28, 2022. The biological material samples for microbiological examination were obtained from the following locations: 1) in the pregnant women and/or puerperia: the posterior vaginal vault, cervical canal, afterbirth, and the uterine cavity; 2) in the newborn infants: the blood, cerebrospinal fluid, tracheal secretions, and the catheter. Results: in 38.1% of puerperia, the caesarean section was performed to deliver a baby. In 513 (26.8%) women in labor and their newborns, microbiological tests were not carried out, as they did not have clinical manifestations of infectious diseases. Based on the monitoring of the results of microbiological examination of the biomaterial samples taken from various loci, the following three groups were formed: group 1 - the samples were taken only from the newborns (n=458); group 2 - the samples were taken only from the mothers (n=294); group 3 - the samples were taken both from the mothers and newborns (n=650). Then, group 3 was divided into the following subgroups: the growth of microorganisms was not detected or the normal flora was found (n=459); the potential causative agents of infectious and inflammatory diseases were found in the mother, but not in the newborn (n=161); the same potential causative agents of infectious and inflammat ory diseases were detected in the newborn and the mother (n=19); different potential causative agents of infectious and inflammatory diseases were found in the newborn and the mother (n=6); potential causative agents of infectious and inflammatory diseases were detected in the newborns, but not in the mothers (n=5). Escherichia coli (31.6%) and Streptococcus agalactiae (15.7%) were the most prevalent microorganisms in the birth canal of the pregnant women and puerperia. In the newborns, the same agents were most frequently found in the blood or the tracheal secretions. Conclusion: the microbiological monitoring of the birth canal of pregnant women and puerperia, as well as of newborn infants is necessary for a timely prevention or treatment of infectious diseases. Keywords: monitoring, microbiota, puerperia, newborns, infection, bacterial carriage. For citation: Boronina L.G., Samatova E.V., Asnovskaya A.G. et al. Monitoring the puerperium microbiota is a necessary condition for diagnosing newborn infections in the early neonatal period. Russian Journal of Woman and Child Health. 2023;6(1):13-19 (in Russ.). DOI: 10.32364/2618-8430-2023-6-1-13-19.